VD_FINDINFO ML / 2016 / 103 vom 27. April 2016 - VD Tribunal cantonal (2016)
DÉCISION D'IRRECEVABILITÉ, DÉPENS, PROCÉDURE SOMMAIRE | 101 al. 1 CPC (CH), 101 al. 3 CPC (CH), 253 CPC (CH), 11 TDC, 3 al. 2 TDC